The Effectiveness of Student Activitysheets with Assessment for Learning Approach in Improving Students’ Problem Solving Skills on Reaction Rate Materials - Eka Saskia Pradita; Muchlis Muchlis; Khoirun Nisa’ (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
One of the key competences in learning chemistry is the capacity to solve problems, although this skill is yet not fully developed in the raction rate content. This study uses student activity sheets (SAS) with an assessment for learning technique on reaction rate material to examine how students' problem-solving skills (PSS) develop after learning. This study used a one-group pretest–posttest design and a pre-experimental methodology. Students in grade XI of high school who used SAS in conjunction with an assessment for learning methodology served as the research subjects. Tests of problem-solving skills administered both before and after therapy served as the data collecting tool. Student answers and the execution of learning activities served as supporting data. A descriptive and quantitative analysis of the data was conducted. With an N-gain value of 0.756 in the high category, the average score increased from 55.3 on the pretest to 88.9 on the posttest, indicating that students' PSS had improved following therapy. Furthermore, the students' active participation in the learning process is demonstrated by the 84.1% response rate to learning and the 92.3% execution of learning activities. These results demonstrate that using SAS for assessment for learning can enhance chemistry instruction focused on enhancing students' PSS with reaction rate materials